2005
DOI: 10.1158/1078-0432.ccr-05-0981
|View full text |Cite
|
Sign up to set email alerts
|

Signal Pathway of Hypoxia-Inducible Factor-1α Phosphorylation and its Interaction with von Hippel-Lindau Tumor Suppressor Protein During Ischemia in MiaPaCa-2 Pancreatic Cancer Cells

Abstract: Purpose and Experimental Design: Previously, we observed that the activation of p38 mitogen-activated protein kinase (MAPK) and c-Jun NH 2 -terminal kinase (JNK1) is mediated through the activation of apoptosis signal^regulating kinase 1 (ASK1) as a result of the reactive oxygen species^mediated dissociation of glutaredoxin and thioredoxin from ASK1. In this study, we examined whether p38 MAPK and JNK1are involved in the accumulation of hypoxia-inducible factor-1a (HIF-1a) during ischemia. Human pancreatic can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 32 publications
2
49
0
Order By: Relevance
“…However, unexpectedly, this induction occurred primarily via UPR-induced potentiation of HIF-1 transcriptional activity, an observation that was extended to an additional HIF target, BNIP3. We report that the UPR enhances the phosphorylation of HIF-1␣, which has been shown previously to enhance its activity (11).…”
supporting
confidence: 65%
“…However, unexpectedly, this induction occurred primarily via UPR-induced potentiation of HIF-1 transcriptional activity, an observation that was extended to an additional HIF target, BNIP3. We report that the UPR enhances the phosphorylation of HIF-1␣, which has been shown previously to enhance its activity (11).…”
supporting
confidence: 65%
“…Lending support to the model's finding that extracellular H 2 O 2 greatly determines the cellular hypoxic response, recent studies have indicated catalase added to cell medium has a strong effect on cell-cell communication in microglia via NO signaling (47). Furthermore, another study showed that an adenovirus containing catalase affected the activity of apoptosis signal-regulating kinase 1, another signaling molecule involved in hypoxia and ischemia, whose activity is dependent on H 2 O 2 and indirectly related to HIF1 (57).…”
Section: Ros In Cancer and In Ischemia (I) H 2 O 2 In Cancermentioning
confidence: 99%
“…MAPK signaling pathways are one the critical mediators of cell growth and have been related to hypoxia [22]. Indeed, it has been reported a direct control of HIF-1alpha by several MAPK [23] and in addition ERK5 has been proposed as a putative target of the VHL signaling axis [7] known to share biological targets with HIF-1alpha [24].…”
Section: Discussionmentioning
confidence: 99%